SUBORDINASI PEREMPUAN DALAM NOVEL PEREMPUAN YANG MENANGIS KEPADA BULAN HITAM KARYA DIAN PURNOMO - Nasyadila Alkhaira (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2023)
This article aims to describe the subordination of women in the Novel Perempuan yang Menangis Kepada Bulan Hitam by Dian Purnomo. This research is a qualitative research with a descriptive method and uses a feminist literary approach. The data in this study are in the form of words, phrases, clauses, sentences, and paragraphs that describe the subordination of women in the Novel Perempuan yang Menangis Kepada Bulan Hitam by Dian Purnomo. The results of the study show that subordination to women appears in stories as a result of customary and cultural constraints. Subordination that occurs in the form of women's status is degraded and does not consider women's existence important. Disclosure of women's subordination in the Novel Perempuan yang Menangis Kepada Bulan Hitam will provide information and knowledge for readers to carry out adat in the right way, so that no more women become victims